Indonesian Mortality-Based Dual Purpose Life Insurance Premium Model with Multiple Decrement and Interest Rate Sensitivity - Aris Pransisco Siringo Ringo; Eli Zulkatri; Ahmad Rhandy Irsandha; Brayen Endo Raldie; Novia Ramadhany Rumengan; Natalie Mawar Desember Desember; Beby Griselda Putri (SPECTA Journal of Technology, 2026)
Endowment life insurance is a product that provides benefits both upon the insured's death and while they remain alive until the end of the contract period. Determining premiums for this product requires a model that can capture multiple types of risk, making the multiple-decrement approach relevant. This study aims to calculate dual-purpose life insurance premiums by considering two causes of termination, namely death and inability to pay (lapse), using Indonesia's TMI 2023 mortality data, the probability of default from the OJK 2025 report, and interest rate sensitivity scenarios. The research methods include compiling life expectancy and active-payment probability tables, determining discount factors based on a deterministic interest rate model across three scenarios (pessimistic, realistic, optimistic), and calculating the present value of benefits and annual premiums for two decrement cases. The results show that premiums are highly sensitive to interest rates. Lower interest rates result in higher premiums, while higher interest rates reduce premiums according to the discount principle. In Case 1 (death) and Case 2 (default), different premium values are obtained due to variations in the decrement probabilities of each risk. Overall, the multiple decrement model proved to provide more accurate calculation results that are in line with the actual risk conditions in Indonesia. This study also identified potential developments by incorporating a stochastic interest rate model and adding other types of decrements to support more comprehensive premium setting for the insurance industry.